Retrospective comparison of laparoscopic versus open appendectomy techniques in a tertiary care hospital in Peshawar Pakistan - Afridi, Noor Sardar; Shah, Amjad Ali; Uzair, Muhammad; Hussain, Aftab; Maryam; Khalil, Jawad (International Journal of Pathology, 2025)
Background: In children and young adults, appendicitis, or inflammation of the vermiform appendix, is the most frequent surgical emergency. This study aims to compare and evaluate results of open appendectomy versus laparoscopic appendectomy as regards the length of surgery, recovery after surgery, bowel movement return, and mobilization.Methods: The research carried out a retrospective analysis on 760 individuals who underwent appendectomy procedures at a Peshawar tertiary care hospital between June 2021 and July 2023. These patients were distributed into OA (open appendectomy) and LA (laparoscopic appendectomy) groups. The following variables such as duration of surgery, postoperative bowel movements, hospital stay, and mobilization were selected from the electronic health record for comparison. Ethical approval for the study was granted by the ethics committee, with the assigned IRB & EC number: PIMC/DMR/7. SPSS version 22.0 was used to analyze the data.Results: Operative intervention time for the LA group (38 minutes) was less than that of the OA group (65 minutes). Time to recover in the postoperative period was faster in LA patients, with 95% having bowel movements by the first day after surgery, as compared to the OA group at 68% and was found statistically significant (p value <0.05). Mobilization for the LA group was faster as they were mobilized at 8 hours compared to the OA patients, who were mobilized only after 34 hours and stayed in the hospital for 6 days and were statistically significant (p value <0.05).Conclusion: Comparing laparoscopic appendectomy to open appendectomy, the former was obviously superior in terms of faster recovery, less operative time, and shorter stay in the hospital.